Effect of Hydrogen in Adsorption and Direct Dissociation of CO on Fe (100) Surface: A DFT Study - Amaya Roncancio, Sebastian (2015)
Density functional theory was employed to investigate the effect of the hydrogen in the adsorption and direct dissociation of CO on Fe (100) surface. The preadsorption of hydrogen with coverages of 0, 1/3 and 2/3 monolayer (ML) was used in the present investigation. In the case of 1/3 ML of hydrogen, two configurations of adsorption were studied. The presence of hydrogen shows a major transference of electronic density rom Fe surface to CO adsorbed, increasing the adsorption energy of CO from 2.00 eV in clean surface, to 2.76 eV in 2/3 ML of hydrogen. Furthermore, the activation barrier for direct dissociation of CO was 1.13 eV and for the recombination energy 2.28 eV on clean Fe (100) surface. In the same way, the activation barrier for CO in the presence of coadsorbed hydrogen was slightly affected presenting values of 1.06 eV and 1.16 eV to 1/3 ML configurations and 0.98 eV for 2/3 ML of hydrogen. Finally, the recombination energy decreases to 1.63 eV and 1.49 eV for 1/3 ML configurations and to 1.23 eV for 2/3 ML of coadsorbed hydrogen. These results indicate that the CO adsorption and dissociation are favored in the presence of hydrogenated surfaces.